Компонентний склад і біологічна активність екстрактів гриба Acremonium spp. - Падалко, С.Ф.; Каменчук, О.П.; Бобик, Л.В. (Фактори експериментальної еволюції організмів, 2014)
Aims. The aim of this research was to study the substances produced by fungus Acremonium and their biological activity. Methods. This study was performed using culture cells of fungi and the tests intended to detect the nature of substances extracted from fungi. Results. It is detected the composition and biological activity of extracts from Acremonium fungi. In extracts was found natural growth regulators cytokinins, auxines and gibberellines. The received extracts showed antifungal activity against fungi Fusarium graminearum, Cocliobolus sativus і Rhizoctonia spp. and stimulatory activity for wheat and corn plants. Conclusions. For the first time it is found that Acremonium fungi produce the natural plant growth regulators auxins, gibberellins and cytokinins. The extracts obtained from Acremonium fungi were individually estimated against some phytopathogenes.

Key words: Acremonium, Fusarium graminearum, Cocliobolus sativus, Rhizoctonia spp., biological activity.